2015
DOI: 10.1177/1475921715604389
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study on integrated structural health monitoring system produced by metal three-dimensional printing

Abstract: Numerous structural health monitoring systems have been investigated extensively in order to enhance safety level and reduce direct operational costs. This work demonstrates the feasibility study of a new concept, the effective structural health monitoring system. The effective structural health monitoring system detects cracks using a system of capillaries incorporated into a structure. The structure with the integrated capillaries is produced by additive manufacturing, a process of adding material layer by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The further the cross section from the neutral axis, the lower the moment of inertia and the higher the nominal stress and the stress at the capillary becomes. More details on the design strategy can be found in the paper of Strantza et al [ 9 ]. After production the specimens were milled to the final dimensions shown in Figure 2 b.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The further the cross section from the neutral axis, the lower the moment of inertia and the higher the nominal stress and the stress at the capillary becomes. More details on the design strategy can be found in the paper of Strantza et al [ 9 ]. After production the specimens were milled to the final dimensions shown in Figure 2 b.…”
Section: Methodsmentioning
confidence: 99%
“…The size of the capillaries can currently vary between 1 and 3 mm in diameter. The response of the structure with and without capillary is demonstrated in [ 9 ] where the eSHM system has proven its effectiveness. The eSHM system does not influence the crack initiation behavior and as a result the fatigue life as it is shown in [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…With over 40 fatigue tests conducted, the eSHM has always successfully detected the fatigue cracks prior to complete fracture. Strantza et al [3] presented that the eSHM system has reached TRL level 3. The capillaries of the eSHM system were produced either using laser based Directed Energy Deposition (DED) [4,5] or laser based Powder Bed Fusion (PBF) [6].…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded in the paper of Strantza et al [9] that-for the considered structure in the paper-the presence of the capillary did not influence the fatigue life negatively, although the cracks initiated from the capillary when positioned close to the specimen edge. Another paper of Strantza et al [10] reported on four point bending test results of test samples with a different layout of the embedded capillaries. It was concluded that the capillary had no crucial influence on the fatigue initiation location for the test specimen and test conditions under investigation.…”
Section: Effective Structural Health Monitoring Systemmentioning
confidence: 99%